TINJAUN KRITIS MANAJEMEN PENDIDIKAN ISLAM: PROBLEM MANAJEMEN PENDIDIKAN ISLAM KLASIK, KONTEMPORER, PROBLEM MANAJEMEN ORGANISASI PENDIDIKAN ISLAM - Rahmawati Rahmawati; Aspiani Hambali; Alfian Aco; Mifta Huljannah; Siti Anisa BM; Muh Al Qahfi; Kamus Kamus (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This article is motivated by the discrepancy between the ideal concept and the actual practice of Islamic education management in educational institutions, both in classical and contemporary contexts. Previous studies have generally discussed Islamic education management separately from historical, philosophical, institutional, or practical perspectives; therefore, few studies have integrated classical problems, contemporary problems, and organizational problems of Islamic education into a single critical analytical framework. This article aims to examine the problems of classical Islamic education management, contemporary Islamic education management, and Islamic educational organizations. This study employed a qualitative approach using library research. The data were obtained from 12 relevant sources, consisting of 11 scientific journal articles and 1 academic book published between 2020 and 2026. The literature was analyzed using content analysis with a thematic-critical approach to identify patterns of problems, root causes, impacts, and directions for managerial solutions. The findings show that classical problems in Islamic education management are mainly related to centralized leadership, weak stakeholder management, and traditional learning methods. Contemporary problems include low professionalism among managers, limited institutional innovation, digitalization challenges, and the suboptimal integration of religious knowledge and modern science. Meanwhile, organizational problems in Islamic education are reflected in weak governance, institutional coordination, human resource competence, and strategic leadership. The conceptual contribution of this article is the proposal of an integrative framework suggesting that the reform of Islamic education management should connect historical dimensions, contemporary challenges, and organizational strengthening through participatory leadership, improvement of managerial competence, digitalization of management, and governance based on Islamic values. ABSTRAK Artikel ini dilatarbelakangi oleh adanya ketidaksesuaian antara konsep ideal dan praktik manajemen pendidikan Islam dalam pengelolaan lembaga pendidikan, baik pada masa klasik maupun kontemporer. Kajian sebelumnya umumnya membahas manajemen pendidikan Islam secara terpisah, baik dari aspek historis, filosofis, kelembagaan, maupun praktis, sehingga belum banyak kajian yang mengintegrasikan problem klasik, problem kontemporer, dan problem organisasi pendidikan Islam dalam satu kerangka analisis kritis. Artikel ini bertujuan untuk mengkaji problem manajemen pendidikan Islam klasik, problem manajemen pendidikan Islam kontemporer, serta problem organisasi pendidikan Islam. Metode yang digunakan adalah pendekatan kualitatif dengan jenis studi kepustakaan. Data diperoleh dari 12 literatur yang relevan, terdiri atas 11 artikel jurnal ilmiah dan 1 buku akademik yang diterbitkan pada rentang tahun 2020–2026. Literatur dianalisis menggunakan teknik analisis isi dengan pendekatan tematik-kritis untuk mengidentifikasi pola masalah, akar persoalan, dampak, dan arah solusi manajerial. Hasil kajian menunjukkan bahwa problem klasik manajemen pendidikan Islam terutama terletak pada kepemimpinan yang sentralistik, lemahnya pengelolaan stakeholder, dan metode pembelajaran yang masih tradisional. Problem kontemporer mencakup rendahnya profesionalitas pengelola, keterbatasan inovasi kelembagaan, tantangan digitalisasi, serta belum optimalnya integrasi ilmu agama dan ilmu pengetahuan modern. Sementara itu, problem organisasi pendidikan Islam tampak pada lemahnya tata kelola, koordinasi kelembagaan, kompetensi sumber daya manusia, dan kepemimpinan strategis. Kontribusi konseptual artikel ini adalah menawarkan kerangka integratif bahwa pembaruan manajemen pendidikan Islam perlu menghubungkan dimensi historis, tantangan kontemporer, dan penguatan organisasi melalui kepemimpinan partisipatif, peningkatan kompetensi pengelola, digitalisasi manajemen, serta tata kelola berbasis nilai-nilai Islam.